Antimicrobial Peptides against Bacterial Pathogens: Innovative Delivery Nanosystems for Pharmaceutical Applications - Esther Imperlini; Federica Massaro; Francesco Buonocore (MDPI AG, 2023)
The introduction of antibiotics has revolutionized the treatment and prevention of microbial infections. However, the global spread of pathogens resistant to available antibiotics is a major concern. Recently, the WHO has updated the priority list of multidrug-resistant (MDR) species for which the discovery of new therapeutics is urgently needed. In this scenario, antimicrobial peptides (AMPs) are a new potential alternative to conventional antibiotics, as they show a low risk of developing antimicrobial resistance, thus preventing MDR bacterial infections. However, there are limitations and challenges related to the clinical impact of AMPs, as well as great scientific efforts to find solutions aimed at improving their biological activity, in vivo stability, and bioavailability by reducing the eventual toxicity. To overcome some of these issues, different types of nanoparticles (NPs) have been developed for AMP delivery over the last decades. In this review, we provide an update on recent nanosystems applied to AMPs, with special attention on their potential pharmaceutical applications for the treatment of bacterial infections. Among lipid nanomaterials, solid lipid NPs and lipid nanocapsules have been employed to enhance AMP solubility and protect peptides from proteolytic degradation. In addition, polymeric NPs, particularly nanogels, are able to help in reducing AMP toxicity and also increasing AMP loading. To boost AMP activity instead, mesoporous silica or gold NPs can be selected due to their easy surface functionalization. They have been also used as nanocarriers for different AMP combinations, thus synergistically potentiating their action against pathogens.